2006
DOI: 10.1097/01.cad.0000236301.12715.6b
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility study and pharmacokinetics of low-dose paclitaxel in cancer patients with severe hepatic dysfunction

Abstract: The aim of this study is to investigate the feasibility and determine the pharmacokinetics of low-dose paclitaxel in cancer patients with severe hepatic dysfunction. This was a prospective study. Patients with liver metastases who had either transaminase serum levels higher than 10 times the upper normal limit or bilirubin serum levels higher than 5 times the upper normal limit were eligible. All patients underwent pharmacokinetic evaluation during the first course of treatment. Pharmacokinetics in severe hepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…A pharmacokinetic-pharmacodynamic model, derived from one of the mentioned studies in 35 patients with solid tumours receiving paclitaxel monotherapy, predicted the following recommendation for the initial paclitaxel dose based on the total bilirubin level: ≤ 1.25 × ULN: 175 mg/m 2 (100% dose), 1.26-2.0 × ULN: 115 mg/m 2 (66%), 2.1-3.5 × ULN: 100 mg/m 2 (57%) and 3.6-10 × ULN: 70 mg/m 2 (40%) [48]. The validity of the recommendation for an initial paclitaxel dose of 40% was confirmed in a pharmacokinetic study in 9 patients with severe hepatic dysfunction caused by liver metastases and a bilirubin level of 3-11 × ULN: Treatment with 70 mg/m 2 paclitaxel was safe and led to adequate plasma concentrations [51]. …”
Section: Resultsmentioning
confidence: 95%
“…A pharmacokinetic-pharmacodynamic model, derived from one of the mentioned studies in 35 patients with solid tumours receiving paclitaxel monotherapy, predicted the following recommendation for the initial paclitaxel dose based on the total bilirubin level: ≤ 1.25 × ULN: 175 mg/m 2 (100% dose), 1.26-2.0 × ULN: 115 mg/m 2 (66%), 2.1-3.5 × ULN: 100 mg/m 2 (57%) and 3.6-10 × ULN: 70 mg/m 2 (40%) [48]. The validity of the recommendation for an initial paclitaxel dose of 40% was confirmed in a pharmacokinetic study in 9 patients with severe hepatic dysfunction caused by liver metastases and a bilirubin level of 3-11 × ULN: Treatment with 70 mg/m 2 paclitaxel was safe and led to adequate plasma concentrations [51]. …”
Section: Resultsmentioning
confidence: 95%
“…[4] Another such study recommended the dose of 70 mg/ m 2 every 2 weeks. [5] Huizing and colleagues studied nine patients with advanced breast cancer receiving paclitaxel 250 mg/ m 2 as a 3-h infusion with subsequent granulocyte–colony stimulating factor support. Two patients with liver function disturbances showed a tendency to higher paclitaxel and 6-alfa hydroxypaclitaxel AUC levels, with more pronounced neuropathy.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of paclitaxel pharmacokinetics in patients with normal or mildly impaired liver function suggested a negative correlation between total bilirubin concentrations and paclitaxel elimination. [1][2][3][4][5][6] Venook et al described higher hematological toxicities in patients with liver dysfunction receiving paclitaxel every 3-weekly over 24 h and over 3 h, and suggested dose reductions as a means of overcoming this toxicity. [2] Wilson et al, in a combined Phase I/II study, studied the pharmacokinetics involved in a 96-h infusion of paclitaxel and found correlations between tumor involvement of the liver, aspartate aminotransferase and total bilirubin concentrations and reduced paclitaxel clearance in patients with advanced breast cancer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations